An optimality analysis of dual-edge dependency in Malay dialects - Kim, Sung-A (Journal of Modern Languages, 2017)
Partial reduplication in Johor and Perak Malay exemplifies non local, dual-edge dependency and subsequent feature-changes. Reduplicative prefixes are determined by both left and right edge segments of a base, skipping intermediate segments. The dual-edge dependency and the subsequent feature changes are sufficiently unusual to merit serious investigation in that it provides a challenge to analyses in derivational frameworks. This paper presents a constraint-based account (McCarthy and Prince 1995; McCarthy 1995) which captures both aspects of these Malay reduplications as an interaction between faithfulness and phonotactic constraints. This paper shows that the unusual reduplicative pattern in these dialects can be successfully subsumed in a general pattern of reduplication under a constraint-based framework.